(untitled) (Research, Society and Development, 2024)
Fanconi Anemia (FA) is an autosomal recessive or X-linked hereditary disease that manifests itself in the first years of life, being responsible for congenital anomalies and progressive bone marrow failure, with aplastic anemia (AA) as its main characteristic. This review article aimed to identify the diagnostic methodologies used to detect AF involving genetic, clinical and laboratory applicability. For this study, electronic scientific databases were consulted, such as the Portal States National Library of Medicine National Institutes of Health (Medline/PubMed), Web Of Science, and Scientific Electronic Library Online (SciELO). A total of 1563 scientific articles were found in English, Spanish and Portuguese, 6 of which were included for analysis. It was demonstrated that there are two chromosomal fragility tests, a molecular biology method and a DNA sequencing method, and that the degree of specificity found in the Western blot and mitomycin C (MMC) methods complement the diagnosis of AF. Diepoxybutane (DEB) differs from Western blot and MMC by being more specific in chromosomal breaks, with next generation sequencing (NGS) being the most specific and most informative as it leads to a personalized approach due to ease of access to somatic variations in tumors and changes in gene expression. Therefore, it is concluded that these methods provide greater diagnostic specificity by identifying the genetic association of SCA and somatic mosaicism, understanding the levels of severity, bringing greater agility in taking therapeutic measures.